Characterizing rainfall patterns and dynamics in the Little Ruaha catchment, southern Tanzania - Mahay, Florence H.; Valimba, Patrick C.; Tumbo, Madaka H.; Izdori, Fides J.; Mwabumba, Mohamed F.; Mbungu, Winfred B. (Frontiers in Water, 2025)
Water resources in many regions are increasingly under pressure due to population growth, agricultural expansion, and climate variability, which presents significant challenges in maintaining sustainable water supplies. The Little Ruaha catchment in Tanzania, a critical area for irrigation, water supply, and hydropower projects, is similarly affected by these pressures. This study was conducted to examine in detail the spatial–temporal variability and trends of rainfall indices to inform sustainable water resource management within the catchment. The study utilized the Mann-Kendall (MK) statistical test at a 95% confidence level (p ≤ 0.05), to assess the onset and cessation of annual and seasonal rainfall trends, with a particular focus on the November to April (NDJFMA) rainfall season. Rainbow statistical software was employed to evaluate rainfall normality and probabilities at 20, 50, and 80% risk levels. Results show decreasing trends in annual rainfall at Kilima station and Iringa Maji but were significant at Kilima station. On the other hand, increasing trends which were not significant at Iringa met and Mafinga stations. In terms of seasonal rainfall, the Iringa Met and Kilima stations demonstrated decreasing trends which were significant at Kilima. In addition, Mafinga and Iringa maji stations exhibited insignificant increasing trend. The results indicate that rain-fed crops in the southern and northeastern regions of the catchment are highly susceptible to drought stress, particularly during the short rainfall season (20% probability). Furthermore, there is a significant risk of water stress for sensitive crops in a typical season (50% probability) in these areas. The study recommends the cultivation of short-cycle crops or the implementation of irrigation strategies in vulnerable locations, along with enhancing water productivity and enforcing water permit regulations to ensure sustainable downstream flows. These findings are crucial for hydrological planning, irrigation management, and the overall sustainability of water resources in the Little Ruaha catchment.